Survei Pengetahuan Penggunaan Obat Antibiotik pada Mahasiswa Non Kesehatan di Banjarmasin - Zaini, Muhammad; Abidin, Taufik; Wati, Vivin Vera (Politeknik Unggulan Kalimantan, 2024)
Antibiotics are substances produced by microorganisms or produced synthetically that can kill and inhibit the development of microorganisms. The relatively high and inappropriate use of antibiotics can cause various problems, especially resulting in bacterial resistance. The level of knowledge about antibiotics that is still low causes inappropriate use of antibiotics. This study aims to determine the level of knowledge of non-health students about the use of antibiotics in Banjarmasin. This research is a descriptive survey research with prospective approach. The target population of this study were 50 non-health students. The research data collection used a questionnaire through google form. The results showed that the level of knowledge about antibiotics which in non-health students averaged 65.4% with a good category. It is necessary to educate about the use of antibiotics among students, so that antibiotics can be consumed appropriately.